2018
DOI: 10.31557/apjcp.2018.19.11.3301
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome and Predictive Factors of Variceal Bleeding in Patients with Hepatocellular Carcinoma in Thailand

Abstract: Objective:Hepatocellular carcinoma (HCC) is common cancer in ASEAN. Variceal bleeding (VB) is considered to be fatal complication of cirrhosis with HCC. However, limited studies were reported in ASEAN. Aim of this study was to evaluate overall survival rate and predictors of VB in HCC patients.Methods:We conducted a retrospective cohort study of HCC patients aged ≥15 years between January 2012-January 2016 and follow up through June 2016 at Thammasat University Hospital, Thailand. Clinical information and radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The aim of this case report is to monitor COVID-19 infection as a possible risk factor that triggers variceal hemorrhage in patients with liver cirrhosis [5] . Severity of the liver disease is a well-established risk factor of variceal hemorhage in cirrhotic patients and has strong association with prognosis [6] . Esophageal variceal bleeding is a fatal complication of cirrhosis and is associated with high mortality [6] and prevention of variceal rupture is a crucial part in the management of cirrhotic patients [1] .…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this case report is to monitor COVID-19 infection as a possible risk factor that triggers variceal hemorrhage in patients with liver cirrhosis [5] . Severity of the liver disease is a well-established risk factor of variceal hemorhage in cirrhotic patients and has strong association with prognosis [6] . Esophageal variceal bleeding is a fatal complication of cirrhosis and is associated with high mortality [6] and prevention of variceal rupture is a crucial part in the management of cirrhotic patients [1] .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the association produced the following comorbidity patterns: HCC, hypertension with diabetes mellitus, coronary heart disease and cerebral infarction; and HCC with hypoproteinemia, electrolyte disorders, gastrointestinal hemorrhage and hemorrhagic anemia. Patients with HCC often suffer from severe cirrhosis, resulting in insufficient synthesis of coagulation factors, and as a result, HCC is often complicated with gastrointestinal bleeding and anemia [40]. However, the mechanism of relationship between electrolyte disorders and gastrointestinal bleeding is still unclear, which needs further experimental analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Morbidity and mortality in patients with HCC are related to both the malignancy and the presence of chronic liver disease. Prophylaxis and treatment of decompensated cirrhosis has been shown to decrease HCC-specific mortality and morbidity in many studies [51,52,53,54,55,56,57]. Nonetheless, in a recent study, Cabibbo et al [58] argued that treatment of hepatitis C in patients with "active" HCC remains controversial as these patients were usually excluded in clinical trials.…”
Section: The Role Of Cirrhosismentioning
confidence: 99%
“…For HBV-related HCCs, treatment of hepatitis can preserve or improve liver function, and may be beneficial for patients undergoing curative therapy, or locoregional therapy/chemotherapy with reasonable life expectancy [59]. In HCC patients with variceal bleeding, 1-year and 2.5-year survival rates were 56.6% and 28.3%, respectively [52]. Kim et al [60] found that primary prophylaxis using a non-selective beta blocker or upper endoscopy with ligation or sclerotherapy for variceal bleeding was associated with a reduced risk of mortality in all patients with HCC (HR 0.54; 95% CI 0.33–0.88; p = 0.014).…”
Section: The Role Of Cirrhosismentioning
confidence: 99%